Efektivitas STEM Terhadap Pemahaman Konsep Kimia Siswa Ditinjau dari Perbedaan Gender - Sri Rosmini, Parida; Sofia, Baiq Fara Dwirani; Savalas, Lalu Rudyat Telly (FKIP University of Mataram, 2025)
This study aims to determine the effectiveness of a lesson using the STEM (Science, Technology, Engineering and Mathematics) approach to students' understanding of chemistry concepts in terms of gender differences. The research method uses a quasi-experimental design by conducting pretest and posttest during learning. Sampling using purposive sampling technique. The sample in this study were 71 students of class XI MIPA 3 and XI MIPA 4 at Terara 1 Public High School, consisting of 36 students in class XI MIPA 3 as the experimental class and 35 students in class XI MIPA 4 as the control class. The data collection technique for this study used multiple choice questions and a questionnaire that had gone through validation tests and reliability tests to get students' understanding of chemistry concepts. The hypothesis test shows moderate criteria and the effect size test obtains a value of 0.3 with moderate criteria. Therefore, it can be concluded that the STEM approach affects students' understanding of concepts and gender does not affect students' understanding of concepts.